Mathematical Representation Ability of Students on Linear Program Material in Terms of Learning Interests in Problem Based Learning - Safa Agrita Hilsania; Masrukan Masrukan (Urogram Studi Pendidikan Matematika, Universitas IVET, 2023)
This study aims to determine the completeness of the implementation of Problem-Based Learning (PBL) to the achievement of students' mathematical representation skills, determine the influence of learning interest on the mathematical representation ability of students in PBL, and describe the mathematical representation skills of students in terms of learning interest. The research method used is a mixed method with a concurrent embedded strategy. The results showed that PBL did not complete the mathematical representation ability of students. This is due to several factors including (1) the difficulties experienced by students in online learning, (2) the time gap between the last meeting of PBL and the mathematical representation ability tests, (3) the weakness of PBL learning that takes a long time, (4) the number of students who are the subject is too little, and (5) the problem of mathematical representation ability test instrument is difficult. Furthermore, there is an influence of learning interest in the mathematical representation ability of students in PBL by 56.2%. Then, the mathematical representation ability of subjects with high and medium categories of learning interest tends to be able to meet the three indicators of mathematical representation ability, while subjects with low categories of learning interest are not able to meet the three indicators of mathematical representation ability. The three indicators of mathematical representation ability are visual representation, Representation of Mathematical Equations or Expressions Ability, and representation of words or written text. Keywords: mathematical representation ability, learning interest, problem-based learning.